Paper coating fluid and paper

A paper coating liquid with fine fibers and specific properties addresses high-speed coating challenges by suppressing penetration and enhancing surface retention, ensuring excellent surface properties and smoothness.

JP7604195B2Active Publication Date: 2024-12-23DAIO PAPER CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2020198728
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-11-30
Publication Date
2024-12-23
Estimated Expiration
2040-11-30

AI Technical Summary

Technical Problem

Existing paper coating liquids face challenges in achieving high-speed coating without excessive penetration into the paper base material, leading to compromised surface properties and increased drying energy requirements.

Method used

A paper coating liquid containing fine fibers with specific properties, including an average fiber width of 20 μm or less, a viscosity of 1,000 cps or less, and a Ti value of 2 or more, applied at speeds of 100 m/min or more, which suppresses penetration and enhances surface retention.

Benefits of technology

The solution enables excellent surface properties and smoothness in high-speed coating applications, maintaining coating on the paper surface without increasing the amount of coating, thus improving paper strength and reducing drying time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007604195000001
    Figure 0007604195000001
  • Figure 0007604195000002
    Figure 0007604195000002
  • Figure 0007604195000003
    Figure 0007604195000003
Patent Text Reader

Abstract

To provide a paper coating liquid which is applicable to high-speed coating and a paper having the paper coating liquid applied on a surface of a paper substrate and hence having excellent smoothness.SOLUTION: The paper coating liquid is a coating liquid which is to be applied on a paper substrate at the amount of coating of 5 g / m2 or under at a coating speed of 100 m / min or over and includes a fine fiber having an average fiber width of 20 μm or under, and B type viscosity (25°C, 60 rpm) of 1,000 cps or under. The paper has this coating liquid applied on a paper substrate.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a paper coating liquid and paper. [Background technology]

[0002] A coating liquid is applied to a paper substrate for the purpose of imparting functions such as slip resistance and moisture resistance, or for the purpose of improving the physical properties of the paper substrate itself, such as improving paper strength and sizing properties (hydrophobicity). On the other hand, the application of the coating liquid is performed, for example, by a size press or a spray nozzle attached to a papermaking machine, and the speed tends to increase year by year. In order to accommodate this increase in speed, it is necessary to, for example, reduce the viscosity of the coating liquid. However, when the viscosity of the coating liquid is reduced, it becomes easier to penetrate into the paper substrate. In some cases, the applied coating liquid is preferably penetrated into the paper substrate, but in other cases, it is not preferable for the coating liquid to penetrate into the paper substrate. In the latter case, it is not possible to deal with the problem by only reducing the viscosity of the coating liquid. In addition, in order to leave the coating liquid on the surface of the paper substrate, it is possible to increase the amount of coating, but increasing the amount of coating requires more drying energy and increases the penetration of the coating liquid into the paper substrate, which has a large impact on the physical properties of the paper substrate.

[0003] Therefore, the use of cellulose nanofibers (CNF) is considered. It is known that cellulose nanofibers have thixotropy (see, for example, Patent Document 1, etc.), and it seems that the use of cellulose nanofibers can improve the applicability of the coating liquid and suppress the penetration at the same time. However, this is a general theory, and it is not clear how cellulose nanofibers should be used specifically. In particular, it is not clear how cellulose nanofibers should be used to respond to high-speed coating at a coating speed of 100 m / min or more. In addition, after the coating liquid is applied, the coating liquid is almost always dried, and if the coating speed is increased, the time until this drying and the time for drying itself are usually shortened. In order to be usable as a coating liquid, it is necessary to make it compatible with such application conditions. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Patent No. 6467536 Summary of the Invention [Problem to be solved by the invention]

[0005] The main problem to be solved by the present invention is to provide a paper coating liquid applicable to high speed coating, and paper in which this paper coating liquid is applied to the surface of a paper base material and therefore has excellent surface properties, preferably smoothness. [Means for solving the problem]

[0006] The means for solving the above problems are as follows.

[0007] (Claim 1 (Means described in Coating amount 5g / m 2 Hereinafter, the coating liquid is applied to a paper substrate at a coating speed of 100 m / min or more. Contains fine fibers with an average fiber width of 20 μm or less, The B-type viscosity (25°C, 60 rpm) is 1,000 cps or less, The Ti value (B-type viscosity at 25°C, 10 rpm / B-type viscosity at 25°C, 100 rpm) is 2 or more. Characterized by Coating fluid for paper.

[0008] (Claim 2 (Means described in The fine fibers are unmodified and have a Brookfield viscosity (25°C, 60 rpm) of 20 cps or more. Claim 1 to The paper coating solution described above.

[0009] (Claim 3 (Means described in Claim 1 or claim 2 The coating liquid according to claim 1 is applied to a paper substrate. The paper is characterized by:

[0010] (Claim 4 (Means described in The paper base material is formed of pulp fibers with an average fiber width of 15 μm or more, The average fiber width of the fine fibers is equal to or less than one-half of the average fiber width of the pulp fibers. Claim 3 The paper described in. Effect of the Invention

[0011] According to the present invention, there is provided a paper coating liquid applicable to high speed coating, and this paper coating liquid is applied to the surface of a paper base material, thereby producing paper with excellent surface properties. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Next, an embodiment of the present invention will be described. Note that the embodiment is an example of the present invention. The scope of the present invention is not limited to the scope of the embodiment.

[0013] The paper coating solution in this form has a coating amount of 5 g / m 2 or less (preferably 0.5 to 5 g / m 2 .) and is suitable for application to a paper substrate at a coating speed of 100 m / min or more (preferably 100 to 1500 m / min). In other words, the paper coating liquid of this embodiment is applicable to high-speed coating, and can retain the coating liquid on the surface of the paper substrate without increasing the amount of coating. In addition, since there is no need to increase the amount of coating, it is easy to improve the smoothness.

[0014] The paper coating liquid of this embodiment contains fine fibers with an average fiber width of 20 μm or less, and has a B-type viscosity (25° C., 60 rpm) of 1,000 cps or less. The paper of this embodiment is formed by coating this paper coating liquid on one or both surfaces of a paper base material. The details are described below.

[0015] (Fine Fiber) The paper coating liquid of this embodiment contains fine fibers, preferably at least one of phosphorous acid-modified fine fibers and unmodified fine fibers, more preferably unmodified fine fibers. The fine fibers increase the hydrogen bond points of the pulp fibers constituting the paper base material, thereby improving the paper strength of the paper base material. In addition, the fine fibers remain on the surface of the paper base material, thereby suppressing the penetration of the paper coating liquid into the paper base material. Furthermore, when the fine fibers are unmodified fine fibers, the viscosity of the paper coating liquid does not become too high, and there is no need to reduce the viscosity of the paper coating liquid by lowering the concentration, etc. Therefore, the paper coating liquid becomes easy to dry, and drying following application of the paper coating liquid is performed effectively. As a result, it can be said to be suitable for high-speed coating.

[0016] In this embodiment, "unmodified" refers to cellulose fibers that have not been chemically modified, such as TEMPO oxidation, modification with phosphorus oxoacids such as phosphoric acid and phosphorous acid, or modification with carbamate. In this regard, when cellulose fibers are chemically modified, the uniformity of the fine fibers obtained by subsequent defibration is generally high. However, chemical modification may cause the viscosity of the paper coating liquid to become too high. In consideration of these factors, it is also a preferred embodiment to use phosphorous-modified fine fibers and unmodified fine fibers in combination. When both phosphorous-modified fine fibers and unmodified fine fibers are used in combination, the blending ratio is, for example, 50:50 to 1:99, preferably 40:60 to 1:99, and more preferably 30:70 to 1:99, based on mass.

[0017] In the present invention, the term "unmodified" is defined as meaning that the hydroxyl groups of the cellulose fibers are not modified.

[0018] On the other hand, in the phosphorous acid-modified fine fibers, some or all of the hydroxyl groups (-OH groups) of the cellulose fibers are modified with a phosphorous acid ester. Preferably, some or all of the hydroxyl groups are substituted with a functional group shown in the following structural formula (1) to introduce (modify, modify) a phosphorous acid ester. Particularly preferably, some of the hydroxyl groups of the cellulose fibers are substituted with a carbamate group to also introduce a carbamate (an ester of carbamic acid).

[0019] [ka]

[0020] In structural formula (1), α is none, R, or NHR. R is a hydrogen atom, a saturated linear hydrocarbon group, a saturated branched hydrocarbon group, a saturated cyclic hydrocarbon group, an unsaturated linear hydrocarbon group, an unsaturated branched hydrocarbon group, an aromatic group, or a group derived from any of these. β is a cation made of an organic or inorganic substance.

[0021] Phosphorous acid esters are compounds in which a hydroxyl group (-OH) and an oxo group (=O) are bonded to a phosphorus atom, and the hydroxyl group provides an acidic proton. Therefore, phosphorous acid esters have a high negative charge, similar to compounds having a phosphoric acid group. Therefore, when phosphorous acid esters are introduced, the repulsion between cellulose molecules becomes stronger, making it easier to defibrate cellulose fibers. Furthermore, when phosphorous acid esters are introduced, the transparency and viscosity of the dispersion are improved. Furthermore, phosphorous acid-modified fine fibers are also cellulose fine fibers, and cellulose fine fibers have thixotropy. Therefore, the coatability is improved, and the paper coating liquid remains on the surface of the paper substrate after coating.

[0022] In particular, when a carbamate is introduced together with the phosphorous acid ester, the transparency and viscosity are further improved. In this regard, when the transparency of the phosphorous acid-modified fine fibers is improved, paper coated with a paper coating solution containing the phosphorous acid-modified fine fibers can be provided with a desired color. In addition, the carbamate has an amino group. Therefore, when the carbamate is introduced, it also has a positive charge. Therefore, it is considered that when the carbamate is also introduced, the charge interaction between the phosphorous acid ester and the carbamate is enhanced, and the viscosity is improved. However, if the viscosity increases too much, the coatability is reduced, so in this respect it is preferable to use unmodified fine fibers.

[0023] The amount of phosphorous acid ester introduced is 0.06 to 3.39 mmol, more preferably 0.61 to 1.75 mmol, and particularly preferably 0.95 to 1.42 mmol per 1 g of cellulose fiber. If the amount introduced is less than 0.06 mmol, the cellulose fiber may not be easily defibrated. In addition, the aqueous dispersion of cellulose fine fibers may become unstable. On the other hand, if the amount introduced exceeds 3.39 mmol, the cellulose fiber may dissolve in water. The amount of phosphorous acid ester introduced is a value evaluated based on elemental analysis. For this elemental analysis, X-Max 50 001 manufactured by Horiba, Ltd. is used.

[0024] The degree of substitution (DS) of the functional group represented by the structural formula (1) is preferably 0.01 to 0.55, more preferably 0.10 to 0.28, and particularly preferably 0.15 to 0.23. If the degree of substitution is less than 0.01, the cellulose fibers may not be easily defibrated. On the other hand, if the degree of substitution is more than 0.55, the cellulose fibers may turn yellow.

[0025] The degree of substitution (DS) of the carbamate group is preferably 0.01 to 0.50, more preferably 0.05 to 0.45, and particularly preferably 0.10 to 0.40. If the degree of substitution is less than 0.01, the transparency and viscosity may not be sufficiently increased. On the other hand, if the degree of substitution is more than 0.50, the cellulose fiber may turn yellow.

[0026] The degree of substitution (DS) refers to the average number of functional groups (functional groups shown in structural formula (1) and carbamate groups) substituted per glucose unit in cellulose. The degree of substitution can be controlled, for example, by the reaction temperature and reaction time. Increasing the reaction temperature or lengthening the reaction time increases the degree of substitution. However, if the degree of substitution increases too much, the degree of polymerization of cellulose decreases significantly.

[0027] The average fiber width (average diameter of a single fiber) of the fine fibers is preferably 20 μm or less, more preferably 1 nm to 20 μm, and particularly preferably 3 nm to 15 μm, regardless of the type of fine fibers such as phosphorous acid-modified fine fibers and unmodified fine fibers (hereinafter the same). If the average fiber width is less than 1 nm, the fibers dissolve in water, and the physical properties of fine fibers, such as viscosity, may become too high, while the strength and dimensional stability may be lost. In addition, if the average fiber width is 20 μm or less, the paper coating liquid does not have excessive viscosity, coating unevenness is suppressed, and the coating thickness can be easily controlled. On the other hand, if the average fiber width exceeds 20 μm, it can no longer be called a fine fiber and becomes no different from a normal cellulose fiber, and for example, thixotropy and the like may not be exhibited, and it may not be suitable for improving paper strength.

[0028] The fiber width of the fine fibers is measured using an electron microscope as follows. First, 100 ml of an aqueous dispersion of fine fibers with a solid content concentration of 0.01 to 0.1% by mass is filtered through a Teflon (registered trademark) membrane filter, and the solvent is replaced once with 100 ml of ethanol and three times with 20 ml of t-butanol. Next, the sample is freeze-dried and osmium-coated to obtain a sample. This sample is observed using an electron microscope SEM image at a magnification of 5000 times, 10,000 times, or 30,000 times depending on the width of the fibers that constitute it. In this observation, two diagonal lines are drawn on the observed image, and three straight lines are arbitrarily drawn that pass through the intersections of the diagonal lines. Then, the widths of a total of 100 fibers that intersect with these three straight lines are visually measured. The median diameter of this measurement is taken as the fiber width.

[0029] The average fiber length of the fine fibers (single fiber length) is preferably 10 nm to 5,000 μm, more preferably 100 nm to 1,000 μm, and particularly preferably 100 nm to 500 μm. If the average fiber length is less than 10 nm, the fibers may become weakly entangled, and the paper strength may not be sufficiently improved. On the other hand, if the average fiber length exceeds 5,000 μm, the fibers may aggregate.

[0030] The average fiber length of the fine fibers can be adjusted as desired by, for example, selecting pulp fibers, pre-treating, and fine fiber refining.

[0031] The average fiber length of the fine fibers is measured by visually measuring the length of each fiber in the same manner as in the case of the average fiber diameter, and the median length of the measured values ​​is taken as the average fiber length.

[0032] The axial ratio of the fine fibers is 3 to 5,000,000, more preferably 6 to 1,000,000, and particularly preferably 10 to 500,000. If the axial ratio is less than 3, it can no longer be said to be fibrous. On the other hand, if the axial ratio exceeds 5,000,000, the viscosity of the paper coating liquid (slurry) becomes too high and the flowability may deteriorate.

[0033] The fibrillation rate of the fine fibers is 50% or more, more preferably 60% or more, and particularly preferably 80% or more. If the fibrillation rate is less than 50%, the water retention ability of the fibers is weak, and the fluidity of the coating material may deteriorate.

[0034] The fibrillation rate refers to the value obtained by disintegrating fine fibers in accordance with JIS-P-8220:2012 "Pulp Disintegration Method" and measuring the resulting disintegrated pulp using FiberLab. (Kajaani).

[0035] The peak value in the pseudo particle size distribution curve of the fine fibers is preferably one peak. When there is one peak, the fine fibers have high uniformity in fiber length and fiber diameter, excellent drying properties, and are suitable for high-speed coating. In addition, when the fiber diameter and fiber length are highly uniform, the fine fibers also have excellent dispersibility and improve coatability.

[0036] The peak value of the fine fibers is, for example, preferably 1000 μm or less, more preferably 900 μm or less, and particularly preferably 800 μm or less. If the peak value exceeds 1000 μm, there is a risk that uniform defibration is not achieved.

[0037] The peak value of the fine fibers is measured in accordance with ISO-13320 (2009). More specifically, a particle size distribution measuring device (a laser diffraction / scattering particle size distribution measuring device manufactured by Seishin Enterprise Co., Ltd.) is used to examine the volumetric particle size distribution in the aqueous dispersion of the fine fibers. The most frequent diameter of the fine fibers is then measured from this distribution. This most frequent diameter is taken as the peak value.

[0038] The crystallinity of the fine fibers is 50 to 95, more preferably 60 to 90, and particularly preferably 65 to 85. If the crystallinity is less than 50, the strength of the fine fibers is low and the effect as a paper strength agent cannot be expected. On the other hand, if the crystallinity is more than 95, the fine cellulose fibers have high rigidity and lack dispersibility. The crystallinity can be adjusted, for example, by selecting pulp fibers, pre-treating, defibrating, etc.

[0039] The crystallinity is a value measured by X-ray diffraction in accordance with JIS-K0131 (1996) "General Rules for X-ray Diffraction Analysis." Note that fine fibers have amorphous and crystalline portions, and the crystallinity refers to the proportion of the crystalline portion in the entire fine fibers.

[0040] When the concentration of the fine fibers is 1% by mass (w / w), the B-type viscosity of the aqueous dispersion is 10 to 300,000 cps, more preferably 50 to 100,000 cps, and particularly preferably 100 to 50,000 cps. If the B-type viscosity is less than 10 cps, the viscosity is too low, so the fluidity of the coating material is high, and the bias of the active ingredient in the coating material may become significant. On the other hand, if the B-type viscosity exceeds 300,000 cps, the viscosity is too high, making coating difficult. Also, if the B-type viscosity exceeds 300,000 cps, it may be difficult to make the B-type viscosity (25°C, 60 rpm) of the paper coating liquid 1,000 cps or less. However, if the B-type viscosity is less than 10, the viscosity of the paper coating liquid may be too low, making it difficult to suppress penetration into the paper substrate.

[0041] It is preferable that the viscosity of the paper coating liquid not containing cellulose is low, and the viscosity of the aqueous dispersion itself is an important factor in preventing penetration (suppressing migration).

[0042] The B-type viscosity (solids concentration 1%) of dispersions containing fine fibers is a value measured in accordance with JIS-Z8803 (2011) "Method of measuring viscosity of liquids." B-type viscosity is the resistance torque when the dispersion is stirred, and the higher the viscosity, the more energy is required for stirring.

[0043] The pulp viscosity of the fine fibers is preferably 1 to 10 cps, more preferably 2 to 9 cps, and particularly preferably 3 to 8 cps. The pulp viscosity is the viscosity of the solution obtained by dissolving cellulose in a copper ethylenediamine solution, and a higher pulp viscosity indicates a higher degree of polymerization of cellulose, which affects the strength of the fibers themselves and the viscosity of the dispersion itself.

[0044] The pulp viscosity of the fine fibers is a value measured in accordance with TAPPI T 230.

[0045] The water retention of the fine fibers is preferably 250 to 500%, preferably 300 to 450%, and more preferably 300 to 400%. If the water retention is less than 250%, the fluidity is low and the smoothness of the resulting paper may be impaired. On the other hand, if the water retention is more than 500%, the drying property is deteriorated. The water retention of the fine fibers can be adjusted as desired, for example, by selecting the raw pulp, pre-treating, defibrating, etc.

[0046] The water retention of fine fibers is a value measured in accordance with JAPAN TAPPI No. 26 (2000).

[0047] The blending ratio of the fine fibers is preferably 1 to 50%, more preferably 2 to 40%, and particularly preferably 3 to 30%, calculated as solid content relative to the entire paper coating liquid. If the blending ratio is less than 1%, the effect of including the fine fibers may not be exhibited. On the other hand, if the blending ratio exceeds 50%, the viscosity may become too high.

[0048] (Method of manufacturing fine fibers) In the case of producing phosphorous-modified fine fibers, an additive (A) consisting of at least one of phosphorous acids and metal phosphorous salts, and preferably an additive (B) consisting of at least one of urea and a urea derivative, is added to cellulose fibers, and heated to introduce phosphorous ester, preferably phosphorous ester and carbamate, into the cellulose fibers. The cellulose fibers into which the phosphorous ester or the like has been introduced are washed and then defibrated to obtain phosphorous-modified fine fibers. However, the introduction of phosphorous ester or carbamate may be performed after defibration (refining). On the other hand, in the case of producing unmodified fine fibers, only defibration or the like is performed without using the additive (A) and the additive (B). This defibration or the like method is the same as that in the case of producing phosphorous-modified fine fibers, so the following will be described using the case of producing phosphorous-modified fine fibers as an example. However, the following will be described using the case of producing phosphorous-modified fine fibers as an example, but as mentioned above, it is not intended that phosphorous-modified fine fibers are preferable to unmodified fine fibers.

[0049] (Cellulose fiber) As the cellulose fiber that is the raw material for the fine fibers, for example, plant-derived fibers (plant fibers), animal-derived fibers, microorganism-derived fibers, etc. can be used. These fibers can be used alone or in combination as necessary. However, as the cellulose fiber, it is preferable to use plant fibers, and it is more preferable to use pulp fibers, which are a type of plant fiber. When the cellulose fiber is pulp fiber, it is easy to adjust the physical properties of the fine fibers, such as phosphorous acid-modified fine fibers.

[0050] Examples of plant fibers that can be used include wood pulp made from broadleaf trees, coniferous trees, etc., non-wood pulp made from straw, bagasse, etc., and waste paper pulp (DIP) made from recycled waste paper, broke paper, etc. These fibers can be used alone or in combination.

[0051] Examples of wood pulp that can be used include chemical pulps such as hardwood kraft pulp (LKP) and softwood kraft pulp (NKP), mechanical pulp (TMP), and deionized paper pulp (DIP), etc. These pulps can be used alone or in combination.

[0052] The hardwood kraft pulp (LKP) may be bleached hardwood kraft pulp, unbleached hardwood kraft pulp, or semi-bleached hardwood kraft pulp. The softwood kraft pulp (NKP) may be bleached softwood kraft pulp, unbleached softwood kraft pulp, or semi-bleached softwood kraft pulp. The deionized paper pulp (DIP) may be magazine waste paper pulp (MDIP), newspaper waste paper pulp (NDIP), corrugated paper pulp (WP), or other deionized paper pulp.

[0053] (Additive (A)) The additive (A) is composed of at least one of phosphorous acids and metal phosphites. As the additive (A), for example, phosphorous acid compounds such as phosphorous acid, sodium hydrogen phosphite, ammonium hydrogen phosphite, potassium hydrogen phosphite, sodium dihydrogen phosphite, sodium phosphite, lithium phosphite, potassium phosphite, magnesium phosphite, calcium phosphite, triethyl phosphite, triphenyl phosphite, pyrophosphorous acid, etc. can be used. These phosphorous acids or metal phosphites can be used alone or in combination. However, it is preferable to use sodium hydrogen phosphite.

[0054] When the additive (A) is added, the cellulose fibers may be in a dry state, a wet state, or a slurry state. The additive (A) may be in a powder state or an aqueous solution state. However, it is preferable to add the additive (A) in an aqueous solution state to the cellulose fibers in a dry state, since this ensures high reaction uniformity.

[0055] The amount of additive (A) added is preferably 1 to 10,000 g, more preferably 100 to 5,000 g, and particularly preferably 300 to 1,500 g, per 1 kg of cellulose fiber. If the amount is less than 1 g, the effect of adding additive (A) may not be obtained. On the other hand, if the amount is more than 10,000 g, the effect of adding additive (A) may reach a plateau.

[0056] (Additive (B)) The additive (B) is at least one of urea and a urea derivative. For example, urea, thiourea, biuret, phenylurea, benzylurea, dimethylurea, diethylurea, tetramethylurea, etc. can be used as the additive (B). These ureas or urea derivatives can be used alone or in combination. However, it is preferable to use urea.

[0057] When the additive (B) is heated, it decomposes into isocyanic acid and ammonia as shown in the following reaction formula (1). The isocyanic acid is highly reactive and forms carbamate groups on the hydroxyl groups of cellulose as shown in the following reaction formula (2).

[0058] NH2-CO-NH2→ HN=C=O+NH3…(1)

[0059] Cell-OH+HN=C=O → Cell-CO-NH2…(2)

[0060] The amount of additive (B) added is preferably 0.01 to 100 mol, more preferably 0.2 to 20 mol, and particularly preferably 0.5 to 10 mol, relative to 1 mol of additive (A). If the amount is less than 0.01 mol, the carbamate may not be sufficiently introduced into the cellulose fiber. On the other hand, even if the amount is more than 100 mol, the effect of adding urea may reach a plateau.

[0061] (heating) The heating temperature when the cellulose fiber to which the additive (A) and the additive (B) have been added is preferably 100 to 210° C., more preferably 100 to 200° C., and particularly preferably 100 to 180° C. If the heating temperature is 100° C. or higher, the phosphorous ester can be introduced. However, if the heating temperature exceeds 210° C., the cellulose is rapidly deteriorated, which may cause coloring or a decrease in viscosity.

[0062] The pH when the cellulose fiber to which the additive (A) and the additive (B) are added is heated is preferably 3 to 12, more preferably 4 to 11, and particularly preferably 6 to 9. The lower the pH, the easier it is to introduce phosphorous ester and carbamate. However, if the pH is less than 3, the deterioration of the cellulose may proceed rapidly.

[0063] The cellulose fibers to which the additives (A) and (B) have been added are preferably heated until the cellulose fibers are dried. Specifically, the cellulose fibers are dried until the moisture content of the cellulose fibers is preferably 10% or less, more preferably 0.1% or less, and particularly preferably 0.001% or less. Of course, the cellulose fibers may be in an absolutely dry state with no moisture.

[0064] The heating time of the cellulose fiber containing the additive (A) and the additive (B) is, for example, 1 to 1,440 minutes, preferably 10 to 180 minutes, and more preferably 30 to 120 minutes. If the heating time is too long, the introduction of phosphorous ester or carbamate may proceed too much. In addition, if the heating time is too long, the cellulose fiber may turn yellow.

[0065] As a device for heating the cellulose fiber to which the additive (A) and the additive (B) have been added, for example, a hot air dryer, a papermaking machine, a dry pulp machine, etc. can be used.

[0066] (Pretreatment) Prior to and / or after the introduction of the phosphorous acid ester into the cellulose fibers, the cellulose fibers may be subjected to a pre-defibration treatment such as beating, if necessary. By subjecting the pulp fibers to a pre-treatment prior to defibration of the cellulose fibers, the number of defibrations can be significantly reduced, and the energy required for defibration can be saved. Note that this pre-treatment can also be applied to unmodified fine fibers when the purpose is to improve the efficiency of defibration.

[0067] The pretreatment of the cellulose fibers can be by physical or chemical means, preferably by physical and chemical means. The pretreatment by physical means and the pretreatment by chemical means can be carried out simultaneously or separately.

[0068] As a pretreatment by a physical method, beating is preferably adopted. When cellulose fibers are beaten, the cellulose fibers are cut into uniform pieces. Therefore, entanglement of the cellulose fibers with each other is prevented (agglomeration is prevented). From this viewpoint, beating is preferably performed until the freeness of the cellulose fibers becomes 700 ml or less, more preferably 500 ml or less, and particularly preferably 300 ml or less.

[0069] The freeness of the cellulose fiber is a value measured in accordance with JIS P8121-2 (2012). The beating can be carried out using, for example, a refiner or a beater.

[0070] Examples of pretreatments by chemical methods include hydrolysis of polysaccharides with an acid (acid treatment), hydrolysis of polysaccharides with an enzyme (enzyme treatment), swelling of polysaccharides with an alkali (alkali treatment), oxidation of polysaccharides with an oxidizing agent (oxidation treatment), reduction of polysaccharides with a reducing agent (reduction treatment), etc. However, as pretreatments by chemical methods, enzyme treatment is preferred, and in addition, one or more treatments selected from acid treatment, alkali treatment, and oxidation treatment are more preferred. Enzyme treatment and alkali treatment will be described below in order.

[0071] As the enzyme used in the enzymatic treatment, it is preferable to use at least one of cellulase enzymes and hemicellulase enzymes, and more preferably to use both in combination. The use of these enzymes makes it easier to defibrate cellulose fibers. Note that cellulase enzymes cause the decomposition of cellulose in the presence of water. Also, hemicellulase enzymes cause the decomposition of hemicellulose in the presence of water.

[0072] Examples of cellulase enzymes that can be used include enzymes produced by the genera Trichoderma (filamentous fungi), Acremonium (filamentous fungi), Aspergillus (filamentous fungi), Phanerochaete (basidiomycetes), Trametes (basidiomycetes), Humicola (filamentous fungi), Bacillus (bacteria), Schizophyllum (basidiomycetes), Streptomyces (bacteria), and Pseudomonas (bacteria). These cellulase enzymes are available as reagents or commercially available products. Examples of commercially available products include Cellulose T2 (manufactured by HPI), Meicerase (manufactured by Meiji Seika Kaisha), Novozym 188 (manufactured by Novozym), Multifect CX10L (manufactured by Genencor), and cellulase enzyme GC220 (manufactured by Genencor).

[0073] As the cellulase enzyme, either EG (endoglucanase) or CBH (cellobiohydrolase) can be used. EG and CBH can be used alone or in combination. They can also be used in combination with a hemicellulase enzyme.

[0074] Examples of hemicellulase enzymes that can be used include xylanase, which is an enzyme that breaks down xylan, mannase, which is an enzyme that breaks down mannan, and arabanase, which is an enzyme that breaks down araban. Also, pectinase, which is an enzyme that breaks down pectin, can be used.

[0075] Hemicellulose is a polysaccharide excluding pectins found between cellulose microfibrils in plant cell walls. Hemicellulose is diverse and differs depending on the type of wood and between the layers of the cell wall. The main component of the secondary wall of softwood is glucomannan, while the main component of the secondary wall of hardwood is 4-O-methylglucuronoxylan. Therefore, when obtaining cellulose fine fibers from softwood bleached kraft pulp (NBKP), it is preferable to use mannase. Also, when obtaining cellulose fine fibers from hardwood bleached kraft pulp (LBKP), it is preferable to use xylanase.

[0076] The amount of enzyme added to cellulose fibers is determined by, for example, the type of enzyme, the type of wood used as raw material (coniferous or broadleaf), the type of mechanical pulp, etc. However, the amount of enzyme added to cellulose fibers is preferably 0.1 to 3 mass%, more preferably 0.3 to 2.5 mass%, and particularly preferably 0.5 to 2 mass%. If the amount of enzyme added is less than 0.1 mass%, the effect of adding the enzyme may not be sufficiently obtained. On the other hand, if the amount of enzyme added is more than 3 mass%, cellulose may be saccharified, and the yield of cellulose fine fibers may decrease. In addition, there is also a problem that the effect improvement commensurate with the increase in the amount added may not be observed.

[0077] When a cellulase enzyme is used as the enzyme, the pH during the enzyme treatment is preferably in the weak acidic range (pH = 3.0 to 6.9) from the viewpoint of the reactivity of the enzyme reaction, whereas when a hemicellulase enzyme is used as the enzyme, the pH during the enzyme treatment is preferably in the weak alkaline range (pH = 7.1 to 10.0).

[0078] The temperature during the enzyme treatment is preferably 30 to 70° C., more preferably 35 to 65° C., and particularly preferably 40 to 60° C., regardless of whether a cellulase enzyme or a hemicellulase enzyme is used as the enzyme. If the temperature during the enzyme treatment is 30° C. or higher, the enzyme activity is less likely to decrease, and it is possible to prevent the treatment time from being prolonged. On the other hand, if the temperature during the enzyme treatment is 70° C. or lower, it is possible to prevent the enzyme from being deactivated.

[0079] The time for the enzyme treatment depends on, for example, the type of enzyme, the temperature of the enzyme treatment, the pH during the enzyme treatment, etc. However, the time for the enzyme treatment is generally 0.5 to 24 hours.

[0080] After the enzyme treatment, it is preferable to inactivate the enzyme. Examples of methods for inactivating the enzyme include a method of adding an alkaline aqueous solution (preferably pH 10 or higher, more preferably pH 11 or higher) and a method of adding hot water at 80 to 100°C.

[0081] Next, the method of alkali treatment will be described.

[0082] As a method for the alkali treatment, for example, there is a method in which the cellulose fibers are immersed in an alkaline solution.

[0083] The alkaline compound contained in the alkaline solution may be an inorganic alkaline compound or an organic alkaline compound. Examples of inorganic alkaline compounds include hydroxides of alkali metals or alkaline earth metals, carbonates of alkali metals or alkaline earth metals, and phosphates of alkali metals or alkaline earth metals. Examples of hydroxides of alkali metals include lithium hydroxide, sodium hydroxide, and potassium hydroxide. Examples of hydroxides of alkaline earth metals include calcium hydroxide. Examples of carbonates of alkali metals include lithium carbonate, lithium hydrogen carbonate, potassium carbonate, potassium hydrogen carbonate, sodium carbonate, and sodium hydrogen carbonate. Examples of carbonates of alkaline earth metals include calcium carbonate. Examples of phosphates of alkali metals include lithium phosphate, potassium phosphate, trisodium phosphate, and disodium hydrogen phosphate. Examples of phosphates of alkaline earth metals include calcium phosphate and calcium hydrogen phosphate.

[0084] Examples of the organic alkali compound include ammonia, aliphatic amines, aromatic amines, aliphatic ammonium, aromatic ammonium, heterocyclic compounds, and their hydroxides, carbonates, phosphates, etc. Specific examples include ammonia, hydrazine, methylamine, ethylamine, diethylamine, triethylamine, propylamine, dipropylamine, butylamine, diaminoethane, diaminopropane, diaminobutane, diaminopentane, diaminohexane, cyclohexylamine, aniline, tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrabutylammonium hydroxide, benzyltrimethylammonium hydroxide, pyridine, N,N-dimethyl-4-aminopyridine, ammonium carbonate, ammonium hydrogen carbonate, diammonium hydrogen phosphate, etc.

[0085] The solvent for the alkaline solution may be either water or an organic solvent, but is preferably a polar solvent (water, a polar organic solvent such as alcohol), and more preferably an aqueous solvent containing at least water.

[0086] The pH of the alkaline solution at 25° C. is preferably 9 or more, more preferably 10 or more, and particularly preferably 11 to 14. When the pH is 9 or more, the yield of cellulose fine fibers is high. However, when the pH exceeds 14, the handling property of the alkaline solution is deteriorated.

[0087] (Washing) The cellulose fibers into which the phosphorous ester or the like has been introduced are preferably washed prior to defibration. By washing the cellulose fibers, by-products and unreacted substances can be washed away. Furthermore, if this washing is performed prior to the alkali treatment in the pretreatment, the amount of alkaline solution used in the alkali treatment can be reduced.

[0088] The cellulose fibers can be washed using, for example, water or an organic solvent.

[0089] (Defibrilization) The cellulose fibers to which phosphorous esters and the like have been introduced are defibrated (fine-refining treatment) after washing. Through this defibration, the pulp fibers are microfibrillated to become cellulose fine fibers (cellulose nanofibers and microfiber cellulose). This defibration method can also be used for unmodified fine fibers.

[0090] When defibrating cellulose fibers, it is preferable to prepare the cellulose fibers in a slurry state. The solid content of this slurry is preferably 0.1 to 5 mass%, more preferably 1 to 4 mass%, and particularly preferably 2 to 3 mass%. When the solid content is within the above range, the cellulose fibers can be defibrated efficiently.

[0091] The cellulose fibers can be defibrated by using one or more means selected from homogenizers such as high-pressure homogenizers and high-pressure homogenizers, high-speed rotary homogenizers, grinders, grinders, and other mill-type friction machines, refiners such as conical refiners and disc refiners, single-shaft kneaders, multi-shaft kneaders, and various bacteria. However, the cellulose fibers are preferably defibrated by using a device or method that uses a water flow, particularly a high-pressure water flow, to finely disperse the cellulose fibers. This device or method results in very high uniformity in the size and uniformity of the dispersion of the resulting cellulose fine fibers. In contrast, for example, when a grinder that grinds between rotating grindstones is used, it is difficult to uniformly finely disperse the cellulose fibers, and in some cases, there is a risk that some fiber lumps will remain undisintegrated.

[0092] Grinders used to defibrate cellulose fibers include, for example, the Masscolloider manufactured by Masuko Sangyo Co., Ltd. Devices that use high-pressure water flow to pulverize materials include, for example, Starburst (registered trademark) manufactured by Sugino Machine Co., Ltd. and Nanovater (registered trademark) manufactured by Yoshida Kikai Kogyo Co., Ltd. High-speed rotary homogenizers used to defibrate cellulose fibers include the Clearmix-11S manufactured by M Technique Co., Ltd.

[0093] In addition, when cellulose fibers are defibrated using both the method of grinding between rotating grinding wheels and the method of refining with a high-pressure water jet, and the resulting fibers are observed under a microscope, it has been found that the fibers obtained using the method of refining with a high-pressure water jet have a more uniform fiber width.

[0094] Defibration using a high-pressure water stream is preferably performed by pressurizing a dispersion of cellulose fibers with a pressure booster to, for example, 50 MPa or more, preferably 75 MPa or more, and more preferably 100 MPa or more (high pressure condition), spraying it from a nozzle with a pore diameter of 50 μm or more, and reducing the pressure so that the pressure difference is, for example, 30 MPa or more, preferably 80 MPa or more, and more preferably 90 MPa or more (reduced pressure condition). The pulp fibers are defibrated by the cleavage phenomenon caused by this pressure difference. If the pressure of the high-pressure condition is low or the pressure difference from the high-pressure condition to the reduced pressure condition is small, the defibration efficiency decreases, and repeated defibration (spraying from the nozzle) becomes necessary to achieve the desired fiber diameter.

[0095] As a device for defibrating with a high-pressure water flow, it is preferable to use a high-pressure homogenizer. A high-pressure homogenizer is a homogenizer capable of ejecting a slurry of cellulose fibers at a pressure of, for example, 10 MPa or more, preferably 100 MPa or more. When cellulose fibers are treated with a high-pressure homogenizer, collisions between the cellulose fibers, pressure differences, microcavitation, etc., occur, and the cellulose fibers are effectively defibrated. Therefore, the number of defibration treatments can be reduced, and the production efficiency of cellulose fine fibers can be improved.

[0096] It is preferable to use a high-pressure homogenizer that causes the cellulose fiber slurry to collide in a straight line. Specifically, for example, a high-pressure homogenizer of the counter-collision type (MICROFLUIDIZER (registered trademark), wet jet mill) is used. In this device, two upstream flow paths are formed so that the pressurized cellulose fiber slurry collide in a counter-collision manner at the junction. The cellulose fiber slurry collides at the junction, and the collided cellulose fiber slurry flows out from the downstream flow path. The downstream flow path is provided perpendicular to the upstream flow path, and a T-shaped flow path is formed by the upstream flow path and the downstream flow path. When such a counter-collision type high-pressure homogenizer is used, the energy provided by the high-pressure homogenizer is converted to collision energy to the maximum extent, so that the cellulose fibers can be defibrated more efficiently.

[0097] The cellulose fibers are preferably defibrated so that the average fiber width, average fiber length, water retention, crystallinity, peak value of pseudo-particle size distribution, pulp viscosity, etc. of the resulting cellulose fine fibers have the desired values ​​or evaluations described above.

[0098] The above describes the cases where the fine fibers are unmodified, and the cases where they are modified with phosphorous acid or carbamate, but the cellulose fibers can also be modified (esterified) with phosphorus oxoacid in general. Esterification with phosphorus oxoacid can be performed, for example, by the method described in JP 2019-199671 A.

[0099] In the fine fibers esterified with phosphorus oxoacid, a part of the hydroxyl groups of the cellulose fibers is preferably substituted with the functional group shown in the following structural formula (2). The amount of the functional group shown in structural formula (2) introduced is 2.0 mmol or more, preferably 2.1 mmol or more, more preferably 2.2 mmol or more per gram of cellulose fibers.

[0100] [ka]

[0101] In structural formula (2), a, b, m, and n are natural numbers.

[0102] At least one of A1, A2, . . ., An and A' is O, and the rest are R, OR, NHR, or none. R is a hydrogen atom, a saturated linear hydrocarbon group, a saturated branched hydrocarbon group, a saturated cyclic hydrocarbon group, an unsaturated linear hydrocarbon group, an unsaturated branched hydrocarbon group, an aromatic group, or a group derived from any of these. α is a cation consisting of an organic or inorganic substance.

[0103] The esterification reaction with phosphorus oxoacids proceeds by adding additives such as phosphorus oxoacids or phosphorus oxoacid metal salts to cellulose fibers and heating. Examples of additives include phosphoric acid, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, triammonium phosphate, ammonium pyrophosphate, ammonium polyphosphate, lithium dihydrogen phosphate, trilithium phosphate, dilithium hydrogen phosphate, lithium pyrophosphate, lithium polyphosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, trisodium phosphate, sodium pyrophosphate, sodium polyphosphate, potassium dihydrogen phosphate, dipotassium hydrogen phosphate, tripotassium phosphate, potassium pyrophosphate, potassium polyphosphate, phosphorous acid, sodium hydrogen phosphite, ammonium hydrogen phosphite, potassium hydrogen phosphite, sodium dihydrogen phosphite, sodium phosphite, lithium phosphite, potassium phosphite, magnesium phosphite, calcium phosphite, triethyl phosphite, triphenyl phosphite, and phosphorous acid compounds. These additives can be used alone or in combination.

[0104] (Other ingredients) In the paper coating solution of this embodiment, in addition to fine fibers, it is suitable to use one or more selected from chemicals such as starch, carboxymethyl cellulose, polyvinyl alcohol, alginic acid, polyacrylamide (PAM), ketene dimer, wax, and latex.

[0105] Specifically, the paper coating liquid may contain, for example, a binder resin. The binder resin has the effect of preventing the fine fibers from peeling off from the surface of the paper substrate. The binder resin is prevented from penetrating into the paper substrate by the fine fibers.

[0106] As the binder resin, for example, one or more types can be selected from latexes, emulsions, water-soluble binders, and the like, such as styrene-butadiene latexes, acrylic emulsions, acrylic-styrene emulsions, vinyl acetate emulsions, ethylene-vinyl acetate emulsions, urethane emulsions, starch, modified starch, and polyvinyl alcohol (PVA), and the like.

[0107] The blending ratio of the binder resin is 30% by mass or less, preferably 2 to 30% by mass, and more preferably 3 to 20% by mass, calculated as solid content based on the total amount of the paper coating liquid. If the blending ratio exceeds 30% by mass, the dispersibility and pseudoplasticity of the paper coating liquid may decrease.

[0108] The blending ratio of the binder resin (mass % converted into solid content) to the fine fibers (mass % converted into solid content) is 10:90 to 90:10, preferably 20:80 to 80:20, and more preferably 30:70 to 70:30. If the blending ratio is less than 10:90, the fine fibers may not be able to be retained on the surface of the paper base material. On the other hand, if the blending ratio is more than 90:10, the coating property of the paper coating liquid and the permeation suppression are good, but delamination may occur in terms of adhesion.

[0109] When the purpose of retaining the paper coating liquid on the surface of the paper substrate is, for example, to impart hydrophobicity, it is preferable to add a water repellent to the paper coating liquid.

[0110] As the water repellent, for example, wax, synthetic resin, and mixtures thereof can be used.

[0111] The blending ratio of the water repellent is 30 to 80 mass%, preferably 40 to 80 mass%, more preferably 50 to 80 mass%, in terms of solid content, based on the total amount of the paper coating liquid. If the blending ratio exceeds 80 mass%, it becomes relatively difficult to blend the fine cellulose component, and the dispersibility and pseudoplasticity of the paper coating liquid may decrease. Also, if the blending ratio is below 30%, the water repellency may not be exhibited.

[0112] (Paper coating fluid) The B-type viscosity of the paper coating liquid at 25°C and 60 rpm is preferably 1000 cps or less, more preferably 10 to 900, and particularly preferably 50 to 800. If the B-type viscosity exceeds 1000 cps, it becomes difficult to form a uniform coated surface at a high speed coating speed of 100 m / min or more. However, if the B-type viscosity is below 50 cps, the penetration into the paper substrate becomes too high, and the coating amount becomes 5 g / m or less. 2 If the thickness is kept to 0.05 mm, the amount of paper coating liquid remaining on the paper substrate surface may be too small, and the smoothness may become insufficient.

[0113] The thixotropy index (Ti value) of the paper coating liquid is preferably 1 or more, more preferably 1 to 20, and particularly preferably 2 to 10. If the Ti value is within this range, the coating liquid can be applied at a coating speed of 100 m / min or more and a coating amount of 3 g / m 2 In the following cases, the balance between the coatability of the paper coating liquid and the inhibition of penetration is maintained.

[0114] In this embodiment, the Ti value is the value obtained by dividing the Brookfield viscosity at 10 rpm by the Brookfield viscosity at 100 rpm when the paper coating liquid is at 25°C. Ti value (25°C) = (B-type viscosity at 10 rpm) / (B-type viscosity at 100 rpm) It is.

[0115] Here, the B-type viscosity is a value measured in accordance with JIS-Z8803 (2011) "Method of measuring viscosity of liquids."

[0116] (paper) The paper of this embodiment is one in which the paper coating liquid is applied to one or both surfaces of a paper base material. The paper of this embodiment may be produced by applying the paper coating liquid to the surface of an existing paper base material such as plain paper or paperboard using a size press or a spray nozzle or the like provided in a papermaking facility (offline coating), or by applying the paper coating liquid to a wet paper during the process of producing the paper base material (online coating).

[0117] In the case of online coating, for example, the paper material (raw material) is sprayed from a head box equipped with a mechanism capable of adjusting the raw material concentration in the width direction, a paper layer is formed in the wire part while dispersing the pulp fibers, dewatered in a press part equipped with a shoe press, and the wet paper is dried in a pre-dryer part. The paper coating liquid of this embodiment is applied to the dried wet paper using a size press (for example, a transfer type such as a gate roll or rod metering, or a two-roll pond type). After coating, the paper is dried, for example, in an after-dryer part, canned by a calendar device if necessary, and wound up by a winder. In particular, in the case of online coating, the time for drying itself and the time until drying are limited, and it is not preferable to lower the concentration of the paper coating liquid, so the significance of the paper coating liquid of this embodiment is outstanding.

[0118] However, in both cases of offline application and online application, it is preferable that the paper base material is formed from pulp fibers with an average fiber width of 15 μm or more (preferably 15 to 30 μm), and the average fiber width of the fine fibers is one-half or less (preferably one-thousandth) of the average fiber width of the pulp fibers constituting the paper base material. In this form, the fine fibers also function as a filler for the paper base material, so that the penetration of the paper coating liquid into the paper base material is further suppressed, the paper strength is further improved, and the surface smoothness is also improved.

[0119] The amount of the paper coating solution applied is, for example, 0.1 to 10 g / m 2 , preferably 0.2 to 5 g / m 2 , more preferably 0.5 to 3 g / m 2 If the coating amount is too small, the amount of paper coating liquid remaining on the surface of the paper substrate will be insufficient, and it may not be possible to achieve the intended purpose of sizing, etc. On the other hand, if the coating amount is too large, coating unevenness may occur even in this embodiment in which the B-type viscosity (25°C, 60 rpm) of the coating liquid is 1,000 cps or less.

[0120] The basis weight of the paper base material is, for example, 15 to 10,000 g / m when the paper base material is plain paper other than paperboard. 2 , preferably 20 to 900 g / m2 , more preferably 30 to 800 g / m 2 On the other hand, when the paper substrate is paperboard, for example, 60 to 1000 g / m 2 , preferably 100 to 500 g / m 2 , more preferably 120 to 480 g / m 2 It is.

[0121] The Beck smoothness of the paper substrate is, for example, 1 second or more, preferably 1 to 1,000 seconds, and more preferably 2 to 500 seconds.

[0122] The nice sizing degree of the paper base material is, for example, 1 to 1,000 seconds, preferably 1 to 500 seconds, and more preferably 2 to 200 seconds. If the sizing degree is too high, the paper base material may repel the paper coating liquid of this embodiment (B type viscosity (25°C, 60 rpm) is 1,000 cps or less), which may result in insufficient application of the coating liquid.

[0123] The raw material for the paper base material can be, for example, the same pulp raw material as the raw material for the fine fibers. It is also preferable to use the same type of raw material, particularly raw materials of the same color, as the raw pulp for the paper base material and the raw pulp for the fine fibers. That is, for example, when the paper base material is white (for example, BKP such as NBKP or LBKP is used as the raw material), it is preferable that the raw material for the fine fibers is BKP, and on the other hand, when the paper base material is brown (for example, UKP such as NUKP or LUKP is used as the raw material), it is preferable that the raw material for the fine fibers is UKP or TMP.

[0124] The effectiveness of this paper is fully demonstrated when it is used as functional liner paper, kraft paper, or base paper for coating in printing (base paper requiring pre-coating), particularly when surface treatment is required to impart water repellency and anti-slip properties. EXAMPLES

[0125] The following describes an embodiment of the present invention. (Test Example 1) The water repellent (Repax A-750 / Toho Chemical Industry Co., Ltd.) was mixed with 30% by mass of mechanically defibrated CNF (average fiber width 50 nm) at 2.0% concentration, polyvinyl alcohol "Poval S-71" at 1.0% concentration as a binder component, and adjusting water to adjust the paint concentration to 4.9%. Then, JEK (manufactured by Daio Paper Co., Ltd., basis weight 280 g / m 2 ) was hand-coated with a wire bar to obtain a liner paper. The physical properties of this liner paper, such as smoothness, were measured. The results are shown in Table 1. Details of the chemicals used, their amounts, etc., are also shown in Table 1. The measurement methods were as described above.

[0126] In addition, the component concentration of the anti-slip agent in the table is 25%, and the component concentration of the water repellent agent is 30%, and the total weight obtained by multiplying the weight of each component used by the component concentration is shown as the "active ingredient." Also, the paint concentration in the table is the ratio of the active ingredient to the total (in its original form) (same below).

[0127] (Test Example 2) Test Example 1 was repeated except that the CNF in Test Example 1 was changed to MFC (average fiber width: 15 μm).

[0128] (Test Example 3) The same procedure as in Test Example 1 was repeated, except that an anti-slip agent (AT3802: Seiko PMC Corporation) was used at a concentration of 25 mass% instead of the CNF used in Test Example 1, and the paint concentration was 5.0%.

[0129] (Test Example 4) 200g of 1.3% polyvinyl alcohol "Poval S-71" was mixed with 80g of 2.0% CNF solution and adjusted water to adjust the paint concentration to 1.3%. Then, a lightweight wrapping paper (manufactured by Daio Paper Co., Ltd., basis weight 50g / m2) was applied. 2 ), high-white recycled PPC paper (manufactured by Daio Paper Co., Ltd., basis weight 66g / m 2 ) was hand-coated with a wire bar. Physical properties such as smoothness were measured.

[0130] (Test Example 5) Test Example 4 was repeated except that the CNF in Test 4 was changed to MFC (average fiber width: 15 μm).

[0131] (Test Example 6) The same procedure as in Test Example 4 was repeated, except that 40 g of a 2.0% solution of unmodified CNF and 40 g of a 1.0% solution of modified CNF were added to 200 g of 1.3% polyvinyl alcohol "Poval S-71" and adjusted to a paint concentration of 1.3%.

[0132] (Test Example 7) The same procedure as in Test Example 4 was repeated, except that 80 g of a 1.5% solution of sodium carboxymethylcellulose (Daicel Finechem product number 1330) was added to 200 g of 1.3% concentration polyvinyl alcohol "Poval S-71" to adjust the paint concentration to 1.1%.

[0133] [Table 1]

[0134] In this embodiment, the JEK liner paper, light packaging paper, and high-white recycled PPC paper are made of different types of pulp, but the average fiber width is 10 to 25 μm and the average fiber length is 0.5 to 3.0 mm, and is adjusted according to the required quality of each paper (fibrillation rate, etc. differ).

[0135] (Consideration) Generally, in high-speed coating, a low-viscosity, low-concentration coating material is used, which tends to penetrate the paper and make it difficult to achieve smoothness. However, the coating material of the present invention contains fine fibers, which inhibits the penetration of the coating material and allows the coating material to remain on the paper surface. As a result, even with the same coating amount, the coating material has high smoothness and excellent high-speed coating properties. [Industrial Applicability]

[0136] The present invention can be used as a paper coating liquid and paper.

Claims

1. A coating solution that is applied to a paper substrate at a coating amount of 5 g / m2 or less and a coating speed of 100 m / min or more, Contains fine fibers with an average fiber width of 20 μm or less, The Brookfield viscosity (25°C, 60 rpm) is 1,000 cps or less, The Ti value (B-type viscosity at 25° C., 10 rpm / B-type viscosity at 25° C., 100 rpm) is 2 or more. A paper coating solution comprising:

2. The fine fibers are unmodified and have a Brookfield viscosity (25°C, 60 rpm) of 20 cps or more. The paper coating solution according to claim 1 .

3. The coating solution according to claim 1 or claim 2 is applied to a paper substrate. The paper is characterized by:

4. The paper base material is formed of pulp fibers with an average fiber width of 15 μm or more, The average fiber width of the fine fibers is equal to or less than one-half of the average fiber width of the pulp fibers. The paper of claim 3.

Citation Information

Patent Citations

  • Heat sensing device for cooking utensil

    JP1989067536A

  • Coated paper having excellent gloss and production thereof

    JP1993009895A

  • Modified finely fibrillated cellulose, method for producing the same, paper sheet incorporated with modified finely fibrillated cellulose, and coated paper produced by using modified finely fibrillated cellulose

    JP2002194691A

  • Coated paper for offset printing

    JP2009263853A

  • Inkjet recording paper and manufacturing process therefor

    JP2018089796A